All-solid-state lithium ion secondary battery and method for manufacturing all-solid-state lithium ion secondary battery

By using amorphous solid electrolyte layer in an all-solid state, specific composition of lithium oxide and lithium salt and vacuum drying treatment in an all-solid state lithium-ion secondary battery, the problems of insufficient conductivity and circulation characteristics are solved, and lithium ions are realized The performance of secondary batteries is improved.

CN119174026APending Publication Date: 2024-12-20INSTITUTE OF SCIENCE TOKYO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039024.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The solid electrolyte layer of the existing all-solid-state lithium-ion secondary battery has insufficient lithium-ion conductivity and there is room for improvement in circulation characteristics, especially when high-temperature sintering treatment and organic polymer blending is not performed.

Method used

A solid electrolyte layer in an amorphous state contains lithium oxides and lithium salts of Li, B and O. The molar ratio of lithium salts is 0.001 to 1.5. The laminate is formed by vacuum drying to ensure the bonding between particles. and lithium ion conductivity.

Benefits of technology

It is realized that an all-solid-state lithium-ion secondary battery with higher lithium ion conductivity, excellent safety and excellent circulation characteristics without high-temperature sintering treatment, and the manufacturing method effectively improves the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174026A_ABST
    Figure CN119174026A_ABST
Patent Text Reader

Abstract

An all-solid-state lithium ion secondary battery in which a positive electrode layer, a solid-state electrolyte layer, and a negative electrode layer are arranged in this order, the solid-state electrolyte layer containing an amorphous solid-state electrolyte containing a lithium-containing oxide containing Li, B, and O, and a lithium salt, and in the amorphous solid-state electrolyte, a lithium salt is contained in the lithium-containing oxide containing Li, B, and O, and a lithium salt is contained in the lithium-containing oxide containing Li, B, and O. The ratio of the content of the lithium salt to the content of the lithium-containing oxide is 0.001-1.5 in terms of molar ratio, and the moisture contained in a laminate comprising the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is in a specific state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid-state lithium-ion secondary battery and a method for manufacturing the all-solid-state lithium-ion secondary battery. Background Art

[0002] In the past, liquid electrolytes with high ion conductivity have been used in lithium-ion secondary batteries. However, since liquid electrolytes are flammable, there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.

[0003] In contrast, all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. The basic structure of an all-solid-state lithium-ion secondary battery is shown in FIG. Figure 1 In the embodiment of the present invention, the all-solid-state lithium-ion secondary battery 10 has a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4 and a positive electrode current collector 5 in order from the negative electrode side. Each layer is in contact with each other and has an adjacent structure. By adopting this structure, during charging, electrons (e - ) is supplied to the negative electrode side, so that the lithium ions (Li + ) accumulates here. On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side through the solid electrolyte layer 3, so that the electrons are supplied to the working part 6. In the example shown in the figure, a light bulb is used as a model at the working part 6, and it is lit by discharge.

[0004] As described above, in order to obtain desired charge and discharge characteristics in an all-solid-state lithium ion secondary battery, the solid electrolyte layer needs to have excellent lithium ion conductivity.

[0005] As the solid electrolyte constituting the solid electrolyte layer, a sulfide-based solid electrolyte or an oxide-based solid electrolyte is mainly used.

[0006] Since sulfide-based solid electrolytes are soft and plastically deformable, the particles can be bonded together simply by press molding. Therefore, the interface resistance between the particles of sulfide-based solid electrolytes is low and the ion conductivity is excellent. However, sulfide-based solid electrolytes have the problem of reacting with water to produce toxic hydrogen sulfide.

[0007] In contrast, oxide-based solid electrolytes have the advantage of high safety. However, oxide-based solid electrolytes are hard and not prone to plastic deformation. In order to improve the adhesion between particles of oxide-based solid electrolytes, high-temperature sintering treatment is required, which is limited from the perspectives of battery production efficiency and energy costs. For example, Patent Document 1 discloses a solid electrolyte formed of a lithium-containing oxide composed of specific elements, and it is recorded that the solid electrolyte shows high ion conductivity, but in order to use the lithium-containing oxide as a solid electrolyte sheet, a high-temperature sintering treatment is required.

[0008] As a technology to deal with this problem, for example, Patent Document 2 describes a composite comprising a lithium compound and lithium tetraborate, wherein the lithium compound has a lithium ion conductivity of 1.0×10 -6 S / cm or more, and the reduced two-body distribution function G(r) of the lithium tetraborate obtained from the total X-ray scattering measurement shows a specific distribution. According to the technology described in Patent Document 2, although the composite is composed of a lithium-containing oxide, lithium tetraborate undergoes plastic deformation between lithium compounds to play a role in connecting lithium compounds. Therefore, even if the composite is not subjected to a high-temperature sintering treatment, it can be formed into a lithium ion conductor showing good lithium ion conductivity by a pressurization treatment.

[0009] Previous technical literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-052755

[0012] Patent Document 2: International Publication No. 2021 / 193204 Summary of the invention

[0013] Technical issues to be solved by the invention

[0014] Although the composite described in the above patent document 2 is composed of lithium-containing oxide, it has a soft property and can ensure the bonding between particles even without sintering treatment and without admixing binders such as organic polymers, and has properties that cannot be achieved by oxide-based solid electrolytes to date. However, the results of research conducted by the present inventors have found that the conductivity of lithium ions is not sufficient to be practical as a solid electrolyte layer of an all-solid-state lithium-ion secondary battery at this stage, and there is room for improvement in practical application.

[0015] The lithium ion conductivity of the solid electrolyte used in the all-solid-state lithium ion secondary battery is a necessary characteristic for the all-solid-state lithium ion secondary battery to work as a battery. In addition, the secondary battery is a battery used for repeated charging and discharging, and the characteristic that the battery performance is not easily deteriorated even if it is repeatedly charged and discharged (cycle characteristics) is also an important characteristic required in the all-solid-state lithium ion secondary battery.

[0016] The object of the present invention is to provide an all-solid-state lithium-ion secondary battery and a method for manufacturing the same, wherein the all-solid-state lithium-ion secondary battery uses a lithium-containing oxide in a solid electrolyte layer, wherein the solid electrolyte layer has excellent adhesion between particles even without undergoing a high-temperature sintering treatment and, for example, without the addition of a binder such as an organic polymer, the lithium ion conductivity is higher, the safety is excellent, and the cycle characteristics are also excellent.

[0017] Means for solving technical problems

[0018] The problems of the present invention are solved by the following means.

[0019] [1]

[0020] An all-solid-state lithium-ion secondary battery is provided, which is composed of a positive electrode layer, a solid electrolyte layer and a negative electrode layer in sequence, wherein:

[0021] The solid electrolyte layer includes an amorphous solid electrolyte, wherein the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O and a lithium salt, wherein the content of the lithium salt in the amorphous solid electrolyte is 0.001 to 1.5 in terms of molar ratio relative to the content of the lithium-containing oxide.

[0022] The laminate composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer has a water content of 7.0 mass % or less based on Karl Fischer titration at 100° C., and the difference in water content based on Karl Fischer titration at 100° C. and 300° C. is 0.1 to 5.0 mass %.

[0023] [2]

[0024] An all-solid-state lithium-ion secondary battery is provided, which is composed of a positive electrode layer, a solid electrolyte layer and a negative electrode layer in sequence, wherein:

[0025] The solid electrolyte layer includes an amorphous solid electrolyte, wherein the amorphous solid electrolyte contains a lithium-containing oxide containing Li, B and O and a lithium salt, wherein the content of the lithium salt in the amorphous solid electrolyte is 0.001 to 1.5 in terms of molar ratio relative to the content of the lithium-containing oxide.

[0026] The stacked body composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer is a stacked body subjected to a vacuum drying treatment.

[0027] 〔3〕

[0028] The all-solid-state lithium-ion secondary battery according to [1] or [2], wherein:

[0029] The lithium-containing oxide comprises Li 2+x B 4+y O 7+z .

[0030] Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3.

[0031] [4]

[0032] The all-solid-state lithium-ion secondary battery according to any one of [1] to [3], wherein

[0033] The above lithium salt is represented by the following formula (1).

[0034] Formula (1) LiN(R f1 SO2)(R f2 SO2)

[0035] In the formula, R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.

[0036] 〔5〕

[0037] The all-solid-state lithium-ion secondary battery according to any one of [1] to [4], wherein

[0038] The lithium-containing oxide is an oxide that has been subjected to mechanical grinding treatment.

[0039] [6]

[0040] The all-solid-state lithium-ion secondary battery according to any one of [1] to [5], wherein

[0041] The all-solid-state lithium-ion secondary battery is an all-solid-state lithium-ion secondary battery formed by sealing a stacked body in which the positive electrode layer, the solid electrolyte layer, and the negative electrode layer are sequentially arranged.

[0042] 〔7〕

[0043] The method for manufacturing an all-solid-state lithium-ion secondary battery according to any one of [1] to [6] comprises the following steps:

[0044] In the production of the all-solid-state lithium-ion secondary battery, after forming a stacked body including the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer, the stacked body is subjected to a vacuum drying treatment.

[0045] In the present invention or the specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0046] Effects of the Invention

[0047] The all-solid-state lithium-ion secondary battery of the present invention uses a lithium-containing oxide in the solid electrolyte layer, and the solid electrolyte layer has excellent bonding between particles even without high-temperature sintering treatment, and, for example, without the addition of a binder such as an organic polymer, has higher lithium ion conductivity, excellent safety, and excellent cycle characteristics. In addition, the method for manufacturing the all-solid-state lithium-ion secondary battery of the present invention is a preferred method for manufacturing the all-solid-state lithium-ion secondary battery of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a cross-sectional view schematically showing an example of the structure of an all-solid-state lithium-ion secondary battery.

[0049] Figure 2 This is a diagram showing an example of an X-ray diffraction pattern for explaining the X-ray diffraction characteristics of the solid electrolyte (I) used in the present invention.

[0050] Figure 3 This is a diagram showing an example of the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I) used in the present invention.

[0051] Figure 4 The solid electrolyte (I) used in the present invention is solidified at 20°C or 120°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0052] Figure 5 It means that the solid state of lithium tetraborate crystals is carried out at 20℃ or 120℃ 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0053] Figure 6 The solid electrolyte (I) used in the present invention is solidified at 20°C. 7 A diagram showing an example of a spectrum obtained during Li-NMR measurement.

[0054] Figure 7 Yes Figure 6Figure 2 shows the peak waveform separation.

[0055] Figure 8 This is a diagram showing an example of the Raman spectrum of the solid electrolyte (I) used in the present invention.

[0056] Fig. 9 This is a diagram showing the Raman spectrum of lithium tetraborate crystals.

[0057] Fig.10 Graph showing the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of powdered Li2B4O7 crystals.

[0058] Fig.11 This is a diagram showing the X-ray diffraction pattern of powdered Li2B4O7 crystals. DETAILED DESCRIPTION

[0059] [All-solid-state lithium-ion secondary battery]

[0060] The all-solid lithium ion secondary battery of the present invention (hereinafter also referred to as "secondary battery of the present invention") is composed of a positive electrode layer, a solid electrolyte layer and a negative electrode layer arranged in this order. The solid electrolyte layer is formed using a solid electrolyte of a specific composition in an amorphous state as described later.

[0061] In the secondary battery of the present invention, the laminated structure of the positive electrode layer, the solid electrolyte layer and the negative electrode layer, the laminated body composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer (the laminated structure without the collector) has a water content based on Karl Fischer titration at 100°C (the water content determined by Karl Fischer titration at 100°C) of 7.0% by mass or less. The water content based on Karl Fischer titration can be determined by the method described in the embodiments described later. The water content of the laminated body composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer based on Karl Fischer titration at 100°C is preferably 6.0% by mass or less, more preferably 5.0% by mass or less, further preferably 4.0% by mass or less, more preferably 3.0% by mass or less, further preferably 2.0% by mass or less, further preferably 1.5% by mass or less, and also preferably 1.0% by mass or less. The water content is usually 0.2% by mass or more, preferably 0.4% by mass or more, more preferably 0.6% by mass or more, and further preferably 0.7% by mass or more. Therefore, the water content of the laminate composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer is preferably 0.2 to 6.0% by mass based on Karl Fischer titration at 100°C, more preferably 0.2 to 5.0% by mass, further preferably 0.4 to 4.0% by mass, further preferably 0.4 to 3.0% by mass, further preferably 0.4 to 2.0% by mass, further preferably 0.6 to 2.0% by mass, and further preferably 0.7 to 1.5% by mass.

[0062] Furthermore, in the secondary battery of the present invention, the water content of the stack composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer based on the Karl Fischer titration method at 300°C is preferably 0.1 to 12.0% by mass, more preferably 0.5 to 10.0% by mass, further preferably 1.0 to 8.0% by mass, further preferably 1.5 to 5.0% by mass, and further preferably 1.5 to 3.0% by mass.

[0063] In the secondary battery of the present invention, the difference in water content of the laminate composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer at 100°C and 300°C based on Karl Fischer titration ([water content based on Karl Fischer titration at 300°C] - [water content based on Karl Fischer titration at 100°C]) is 0.1 to 5.0% by mass. The difference in water content is preferably 0.5 to 5.0% by mass, more preferably 1.0 to 5.0% by mass, further preferably 2.0 to 5.0% by mass, further preferably 3.0 to 5.0% by mass, and also preferably 3.0 to 4.0% by mass. Furthermore, the difference in water content is also preferably 0.1 to 4.0% by mass, also preferably 0.5 to 4.0% by mass, also preferably 0.5 to 3.0% by mass, also preferably 0.5 to 2.0% by mass, and also preferably 0.5 to 1.5% by mass.

[0064] Each layer of the secondary battery of the present invention will be described.

[0065] <Solid electrolyte layer>

[0066] The solid electrolyte layer constituting the secondary battery of the present invention is a solid electrolyte of a specific composition in an amorphous state (same meaning as non-crystalline state or amorphous state) or a mixture of the solid electrolyte and other components formed into a layer, usually a layer formed by vacuum drying. The solid electrolyte of a specific composition in an amorphous state before the layer is formed contains a lithium-containing oxide (hereinafter also referred to as "lithium-containing oxide") containing Li, B and O, a lithium salt and water. In the solid electrolyte in an amorphous state before the layer is formed, the ratio of the content of the lithium salt to the content of the lithium-containing oxide (lithium salt / lithium-containing oxide) is 0.001 to 1.5 in terms of molar ratio. Therefore, in the secondary battery of the present invention, the ratio of the content of the lithium salt in the solid electrolyte layer to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio. In addition, in the solid electrolyte in an amorphous state before the layer is formed, the ratio of the content of water to the content of the lithium-containing oxide (water / lithium-containing oxide) is preferably 1 to 12 in terms of molar ratio. Hereinafter, the solid electrolyte of a specific composition in the amorphous state is also referred to as "solid electrolyte (I)". The solid electrolyte (I) is usually an inorganic solid electrolyte.

[0067] The solid electrolyte (I) is in an amorphous state and exhibits elastic properties that are prone to plastic deformation. As a result, in a solid electrolyte layer comprising a solid electrolyte (I) formed by pressurization treatment, drying treatment, etc., the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other ion conductors is improved, and the interface resistance can be reduced, thereby obtaining a more excellent ion conductivity. By using the solid electrolyte (I) to form a solid electrolyte layer, a lithium ion conductor can be formed, which is a highly safe oxide-based solid electrolyte, but even without high-temperature sintering treatment, it can also show excellent lithium ion conductivity by pressurization treatment, etc.

[0068] The water contained in the solid electrolyte (I) at least includes bound water. Although the reason why the solid electrolyte (I) exhibits high lithium ion conductivity is not clear, in the amorphous solid electrolyte (I), a soft hydration layer is easily formed on the surface of the lithium-containing oxide, and a large amount of lithium derived from the lithium salt is contained in the hydration layer, and as a result, it is believed that the ion conductivity is further improved.

[0069] Here, in the present invention or the specification, "bound water" refers to water other than water existing as free water or OH groups bonded to lithium-containing oxides. Even if the solid electrolyte (I) contains the above-mentioned amount of water, it is in the state of solid particles (including the state in which the solid particles are bonded to each other). That is, the solid electrolyte (I) contains bound water that is not removed or difficult to remove under normal drying conditions. In addition, as long as the solid electrolyte (I) can maintain the state of solid particles, part of the water contained in the solid electrolyte (I) can be free water. In the case where free water is contained in the solid electrolyte (I), at least a part of the free water is removed by the drying treatment described later of the solid electrolyte layer (a laminate composed of a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer) formed by using the solid electrolyte (I). In addition, sometimes, according to the interaction between the bound water and the lithium-containing oxide or lithium salt, and according to the level of the above-mentioned drying treatment conditions, a part of the bound water is removed.

[0070] In the present invention, the solid electrolyte (I) being in an "amorphous state" means that it satisfies the following X-ray diffraction characteristics.

[0071] (X-ray diffraction characteristics)

[0072] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from X-ray diffraction measurement using CuKα rays, a first peak having a peak top located in the range of a diffraction angle 2θ of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top located in the range of a diffraction angle 2θ of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top located in the range of a diffraction angle 2θ of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top located in the range of a diffraction angle 2θ of 34.4 to 34.8° and a full width at half maximum of 0.65° or less are not present, or

[0073] In the X-ray diffraction pattern, when at least one of the above-mentioned 1st peak, 2nd peak, 3rd peak and 4th peak (hereinafter referred to as "peak X") is present, the intensity ratio of at least one of the peaks X calculated by the intensity measurement method described below is 5.0 or less.

[0074] - Strength measurement method -

[0075] The arithmetic mean of Av1 and Av2 is calculated by calculating the average intensity (Av1) in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the peak X, and calculating the average intensity (Av2) in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the peak X. The ratio of the peak intensity at the peak top of the peak X to the arithmetic mean (peak intensity at the peak top of the peak X / arithmetic mean) is taken as the intensity ratio.

[0076] The X-ray diffraction characteristics will be described in more detail.

[0077] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned first peak, second peak, third peak and fourth peak do not exist, the above-mentioned X-ray diffraction characteristics are satisfied and the solid electrolyte (I) is in an amorphous state.

[0078] Furthermore, in the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, when the above-mentioned peak X is present, when the intensity ratio of at least one peak among the peaks X obtained by the above-mentioned intensity measurement method also satisfies 5.0 or less, the above-mentioned X-ray diffraction characteristics are also satisfied, and the solid electrolyte (I) is in an amorphous state.

[0079] Here, the full width at half maximum (FWHM) of the peak refers to the peak width (°) at a point where the peak intensity at the top of the peak is 1 / 2.

[0080] refer to Figure 2, the above-mentioned intensity measurement method is explained in more detail.

[0081] Figure 2 This is a diagram showing an example of a peak X appearing in a diffraction pattern obtained from X-ray diffraction measurement using CuKα rays of a solid electrolyte (I). Figure 2 In the diffraction pattern shown, the intensity of the peak top is shown to show a specific peak with an intensity of 1. In the intensity measurement method, as Figure 2 As shown, the average intensity (Av1) in the range of +0.45° to +0.55° is calculated from the diffraction angle 2θ of the peak top of the peak X, and the average intensity (Av2) in the range of -0.55° to -0.45° is calculated from the diffraction angle 2θ of the peak top of the peak X. Next, the arithmetic mean of Av1 and Av2 is calculated, and the ratio of intensity 1 to the arithmetic mean is obtained as the intensity ratio. When the above-mentioned X-ray diffraction characteristics are met, it means that there is no crystal structure or almost no crystal structure in the solid electrolyte (I) and it is in an amorphous state.

[0082] That is, the 1st peak to the 4th peak mentioned above are peaks mainly derived from the crystal structure (for example, the crystal structure of lithium tetraborate) in the solid electrolyte, and the absence of these peaks means that it is in an amorphous state. And, even in the case where there is at least one peak in the 1st peak to the 4th peak, the intensity ratio of at least one peak in the peak X that exists is 5.0 or less, which means that in the solid electrolyte (I), there is almost no crystal structure that hinders the effect of the present invention. In addition, for example, the peak derived from a specific component (for example, a lithium salt) sometimes overlaps with any one of the 1st peak to the 4th peak mentioned above. However, in a solid electrolyte in an amorphous state, the 1st peak to the 4th peak usually decreases, so even if it is assumed that the peak caused by the above-mentioned specific component coincidentally overlaps with any one of the 1st peak to the 4th peak to appear a large peak, there is at least one peak X with an intensity ratio below a specified value, which can be said to indicate that the solid electrolyte (I) is in an amorphous state.

[0083] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.

[0084] In the X-ray diffraction pattern of the solid electrolyte (I) obtained from the X-ray diffraction measurement using CuKα rays, even if none of the above-mentioned first peak, second peak, third peak and fourth peak exists, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is 3.0 or less.

[0085] Among them, even if the above-mentioned first peak, second peak, third peak and fourth peak do not exist, or at least one peak X among the above-mentioned first peak, second peak, third peak and fourth peak exists, it is preferred that the intensity ratio of at least one peak X is less than 2.0.

[0086] In addition, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 21.6 to 22.0° and a half-width of 0.65° or less, the peak with the largest diffraction X-ray intensity is selected as the first peak to determine the above-mentioned X-ray diffraction characteristics.

[0087] Furthermore, in the above-mentioned X-ray diffraction pattern, when there are two or more peaks with peak tops in the range of 25.4 to 25.8° and a full width at half maximum of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the second peak to perform the above-mentioned X-ray diffraction characteristics.

[0088] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 33.4 to 33.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the third peak to determine the above-mentioned X-ray diffraction characteristics.

[0089] Furthermore, in the above-mentioned X-ray diffraction spectrum, when there are two or more peaks with peak tops in the range of 34.4 to 34.8° and a half-width of less than 0.65°, the peak with the largest diffraction X-ray intensity is selected as the fourth peak to determine the above-mentioned X-ray diffraction characteristics.

[0090] (Total X-ray Scattering Properties)

[0091] The solid electrolyte (I) preferably satisfies the following requirement A-1 as the total X-ray scattering property. Furthermore, when the solid electrolyte (I) satisfies the above-mentioned X-ray diffraction property, the solid electrolyte (I) usually satisfies the following requirement A-2.

[0092] - Requirement A-1-

[0093] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak and the peak top in the range of r are The second peak in the range of , the peak G(r) of the first peak shows more than 1.0, and the peak G(r) of the second peak shows more than 0.8.

[0094] - Requirement A-2-

[0095] In the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), when r is greater than and The absolute value of G(r) in the following range is less than 1.0.

[0096] When the solid electrolyte (I) satisfies requirements A-1 and A-2, it has a short-range ordered structure related to the interatomic distance of BO and BB, but has almost no long-range ordered structure, so the oxide solid electrolyte itself shows elastic properties that are softer and more susceptible to plastic deformation than conventional lithium-containing oxides. As a result, it is speculated that in the layer containing the solid electrolyte (I) formed by pressure treatment, the adhesion between the solid electrolytes (I) and / or the adhesion between the solid electrolyte (I) and other ion conductors is improved, and the interface resistance can be reduced, thereby obtaining more excellent ion conductivity.

[0097] The requirements A-1 and A-2 will be described in more detail with reference to the drawings.

[0098] Figure 3 An example of the reduced two-body distribution function G(r) obtained by total X-ray scattering measurement of the solid electrolyte (I) is shown. Figure 3 The vertical axis is the reduced two-body distribution function obtained by Fourier transform of X-ray scattering, which represents the probability of the existence of an atom at a distance r. Total X-ray scattering measurements can be performed using SPring-8 BL04B2 (acceleration voltage 61.4 keV, wavelength The scattering intensity I obtained by the experiment is transformed according to the following steps to obtain the reduced two-body distribution function G(r).

[0099] First, the scattering intensity I obs It is represented by the following formula (1). And, as shown in the following formula (2), the structure factor S(Q) is obtained by dividing the coherent scattering I coh It is obtained by dividing by the product of the number of atoms N and the square of the atomic scattering factor f.

[0100] I obs =I coh +I incoh +I 荧光 (1)

[0101] [Formula 1]

[0102]

[0103] The structure factor S(Q) is used in PDF (Pair Distribution Function) analysis. In the above equation (2), the required intensity is only the coherent scattering I coh . Incoherent scattering I incoh and Fluorescent X-ray I 荧光 can be used to subtract the theoretical formula using a blank measurement and the detector's discriminator from the scattered intensity I obs Minus.

[0104] Coherent Scattering I coh It is expressed by Debye's scattering formula (the following formula (3)) (N: total number of atoms, f: atomic scattering factor, r ij : the interatomic distance between ij).

[0105] [Formula 2]

[0106]

[0107] If we focus on any atom and let the atomic density at a distance r be ρ(r), then the number of atoms existing in a sphere with a radius of r-r+d(r) is 4πr. 2 ρ(r)dr, the above formula (3) is expressed by the following formula (4).

[0108] [Formula 3]

[0109]

[0110] If the average density of atoms is set to ρ0 and the above formula (4) is modified, the following formula (5) can be obtained.

[0111] [Formula 4]

[0112]

[0113] The following formula (6) can be obtained from the above formula (5) and formula (2).

[0114] [Formula 5]

[0115]

[0116] The two-body distribution function g(r) is expressed by the following equation (7).

[0117] [Formula 6]

[0118]

[0119] The following formula (8) can be obtained from the above formula (6) and formula (7).

[0120] [Formula 7]

[0121]

[0122] As mentioned above, the two-body distribution function can be obtained by Fourier transforming the structure factor S(Q). In order to easily observe the medium-range order / long-range order, the two-body distribution function is transformed into a function G(r)=4πr(g(r)-1) to reduce the two-body distribution function ( Figure 3 ). g(r) oscillating around 0 represents the density difference from the average density at each interatomic distance, and when there is a correlation at a specific interatomic distance, the average density becomes higher than 1. Therefore, the distance and coordination number of the element corresponding to the local to the intermediate distance are reflected. If the order disappears, ρ(r) approaches the average density, so g(r) gradually approaches 1. Therefore, in an amorphous structure, since the larger r becomes, the more the order disappears, g(r) becomes 1, that is, G(r) becomes 0.

[0123] In Element A-1, if Figure 3 As shown, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of the solid electrolyte (I), there is a peak located at r The first peak P1 and the peak top are located at r within the range of In the second peak P2 within the range of , the peak G(r) of the first peak P1 shows a value greater than 1.0 (preferably greater than 1.2), and the peak G(r) of the second peak P2 shows a value greater than 0.8 (preferably greater than 1.0).

[0124] In addition, Figure 3 The peak of the first peak P1 is located at The peak of the second peak P2 is located at

[0125] exist There is a peak at the position of B (boron)-O (oxygen) interatomic distance. There is a peak of the interatomic distance attributed to B (boron)-B (boron) at the position. That is, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the solid electrolyte (I).

[0126] Furthermore, in Element A-2, if Figure 3 As shown, when r is more than and In the following range, the absolute value of G(r) is less than 1.0. As mentioned above, when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, it means that there is almost no long-range ordered structure in the solid electrolyte (I).

[0127] In addition, in the above-mentioned reduced two-body distribution function G(r), when r is In the following range, there are peaks other than the first peak and other than the second peak.

[0128] The method for making the solid electrolyte (I) into an amorphous state is not particularly limited. For example, there is the following method: in the preparation of the solid electrolyte (I), a lithium-containing oxide subjected to mechanical grinding is used as a raw material of the lithium-containing oxide. The mechanical grinding treatment can also be performed in the presence of a lithium salt.

[0129] -Mechanical grinding treatment-

[0130] Mechanical grinding treatment refers to a process of pulverizing a sample while imparting mechanical energy to the sample. As mechanical grinding treatment, for example, a ball mill, a vibration mill, a turbine mill and a disc mill can be mentioned. From the viewpoint of obtaining an amorphous solid electrolyte (I) with good productivity, a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be mentioned, and a planetary ball mill is more preferred.

[0131] The conditions of the ball milling treatment can be appropriately adjusted according to the treatment object. The material of the grinding ball (medium) is not particularly limited, for example, agate, silicon nitride, zirconium oxide, aluminum oxide and iron alloys can be mentioned, preferably yttria stabilized zirconia (YSZ). The average particle size of the grinding ball is not particularly limited. From the perspective of being able to manufacture the solid electrolyte (I) with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is the value obtained by randomly measuring the diameters of 50 grinding balls and arithmetically averaging these. In the case where the grinding ball is not spherical, the major diameter is set as the diameter. The number of grinding balls is not particularly limited.

[0132] The material of the pulverizing pot in the ball milling treatment is not particularly limited, and examples thereof include agate, silicon nitride, zirconium oxide, aluminum oxide, and iron-based alloys, and yttria-stabilized zirconia (YSZ) is preferred.

[0133] The rotation speed of the ball milling process is not particularly limited, and can be set to 200 to 700 rpm, more preferably 350 to 550 rpm. The treatment time of the ball mill is not particularly limited, and can be set to 10 to 200 hours, more preferably 20 to 140 hours. The atmosphere of the ball milling process can be the atmosphere or an inert gas (e.g., argon, helium, nitrogen, etc.) atmosphere.

[0134] In the production of the solid electrolyte (I), the following steps 1A to 3A are preferably performed.

[0135] Step 1A: A step of mechanically grinding a lithium-containing oxide in the presence of a lithium salt

[0136] Step 2A: Step of mixing the product obtained in step 1A with water

[0137] Step 3A: A step of removing water from the dispersion obtained in step 2A to obtain a solid electrolyte (I)

[0138] In step 1A, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.

[0139] In the above step 2A, the amount of water used is not particularly limited. For example, the amount of water used can be 10 to 200 parts by mass, more preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.

[0140] The method of mixing the product obtained in step 1A and water is not particularly limited, and they can be mixed together or water can be added to the product obtained in step 1A in stages for mixing. During mixing, ultrasonic treatment can be performed as needed. The time of ultrasonic treatment is not particularly limited, and can be set to 10 minutes to 5 hours, for example.

[0141] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain solid electrolyte (I). The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water can be removed by heating treatment or vacuum drying treatment.

[0142] Prior to the step 1A, a step 0 of subjecting the lithium-containing oxide to mechanical milling in an environment without the presence of a lithium salt may be performed.

[0143] In the production of the solid electrolyte (I), it is also preferable to carry out the following steps 1B to 3B instead of the above steps 1A to 3A.

[0144] Step 1B: Mechanical grinding of lithium-containing oxide

[0145] Step 2B: Step of mixing the product obtained in step 1B, water and lithium salt

[0146] Step 3B: A step of removing water from the dispersion obtained in step 2B to obtain a solid electrolyte (I)

[0147] The difference between step 1B and step 1A is that in step 1A, the mechanical milling treatment is carried out in the presence of a lithium salt, whereas in step 1B, the mechanical milling treatment is carried out without using a lithium salt. Therefore, in step 2B, the product obtained in step 1B, water, and a lithium salt are mixed.

[0148] The steps of step 2B are not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a lithium salt all together (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a lithium salt (method 2), or a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing a lithium salt and water to prepare a solution 2, and then mixing the dispersion 1 and the solution 2 (method 3). When mixing the product obtained in step 1B and water, a dispersion treatment such as an ultrasonic treatment may be appropriately performed.

[0149] In method 2, when the dispersion obtained by mixing the product obtained in step 1B and water and the lithium salt are mixed, if there is too much lithium salt, the obtained liquid is easily gelled, and the mixing amount of the lithium salt is limited. In contrast, in method 3, even if the product obtained in step 1B and the lithium salt are mixed in approximately equimolar amounts, the liquid is not easily gelled, and the mixing amount of the lithium salt can be further increased. From this point of view, method 3 is preferred.

[0150] Step 3B is the same as step 3A.

[0151] In the production of the solid electrolyte (I), it is also preferable to perform the following steps 1C to 3C instead of the above steps 1A to 3A.

[0152] Step 1C: Step of mechanically grinding the lithium-containing oxide

[0153] Step 2C: Step of mixing the product obtained in step 1C with water

[0154] Step 3C: A step of mixing a product obtained by removing water from the dispersion obtained in step 2C with a lithium salt to obtain a solid electrolyte (I)

[0155] Step 1C is the same as step 1B.

[0156] Step 2C is the same as step 2A.

[0157] Step 3C is different from Steps 3A and 3B in that a product obtained by removing water from the dispersion obtained in Step 2C and a lithium salt are mixed.

[0158] In step 3C, the amount of the lithium salt used is not particularly limited and can be appropriately adjusted to obtain the solid electrolyte (I) specified in the present invention.

[0159] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the lithium salt is not particularly limited, and may be a method of immersing a solution obtained by dissolving the lithium salt in water in the product and mixing the two.

[0160] (Component composition of solid electrolyte (I))

[0161] As described above, the solid electrolyte (I) used in the present invention is an amorphous solid electrolyte, in which the ratio of the lithium salt content to the lithium oxide content is 0.001 to 1.5 in molar ratio, and the ratio of the water content to the lithium oxide content is 1 to 12 in molar ratio.

[0162] The ratio of the content of the lithium salt in the solid electrolyte (I) to the content of the lithium-containing oxide is preferably 0.001 to 1.2, more preferably 0.01 to 1.2, further preferably 0.1 to 1.2, and particularly preferably 0.5 to 1.2 in terms of molar ratio.

[0163] The molar ratio of the water content in the solid electrolyte (I) to the lithium-containing oxide content is more preferably 2 to 12, and further preferably 3 to 11. The molar ratio is also preferably 2 to 10, 2 to 8, 2 to 7, and 3 to 7.

[0164] The molar amounts of the lithium-containing oxide, lithium salt and water in the solid electrolyte (I) can be determined by elemental analysis. Furthermore, the molar amount of water can also be determined by the Karl Fischer method or the like.

[0165] The water content of the solid electrolyte (I) is preferably 50% by mass or less, more preferably 45% by mass or less, further preferably 40% by mass or less, and further preferably 35% by mass or less. In addition, the water content in the solid electrolyte (I) is also preferably 30% by mass or less, and also preferably 25% by mass or less.

[0166] And, the content of water in the solid electrolyte (I) is usually 5% by mass or more, preferably 10% by mass or more, and preferably 15% by mass or more. Therefore, the content of water in the solid electrolyte (I) is preferably 5 to 50% by mass, more preferably 5 to 45% by mass, further preferably 10 to 40% by mass, further preferably 10 to 35% by mass, also preferably 10 to 30% by mass, also preferably 15 to 30% by mass, and also preferably 15 to 25% by mass.

[0167] The content of the lithium-containing oxide in the solid electrolyte (I) is preferably 20 to 80% by mass, more preferably 20 to 75% by mass, and further preferably 25 to 70% by mass.

[0168] The content of the lithium salt in the solid electrolyte (I) is preferably 0.5 to 60% by mass, more preferably 1.0 to 55% by mass, further preferably 2.0 to 50% by mass, and still more preferably 5.0 to 50% by mass.

[0169] -Contains lithium oxide-

[0170] As described above, the lithium-containing oxide constituting the solid electrolyte (I) contains Li, B, and O.

[0171] The lithium-containing oxide is preferably composed of Li 2+x B 4+y O 7+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). That is, when the molar amount of B is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 2.49 (i.e., 1.7×4 / 4.3 to 2.3×4 / 3.7), and the molar amount of O is 6.23 to 7.89 (i.e., 6.7×4 / 4.3 to 7.3×4 / 3.7). In other words, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 2.49, and the molar amount of O is 6.23 to 7.89. As such a lithium-containing oxide, typically lithium tetraborate (Li2B4O7) can be cited.

[0172] Furthermore, the lithium-containing oxide is preferably composed of Li 1+x B 3+y O 5+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). Such lithium-containing oxides typically include lithium triborate (LiB3O5).

[0173] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 11+y O 18+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3) is a compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B 11 O 18 .

[0174] Furthermore, the lithium-containing oxide is preferably composed of Li 3+x B 7+y O 12+z (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). As such lithium-containing oxides, Li3B7O is typically mentioned. 12 .

[0175] Therefore, the lithium-containing oxide is preferably the Li 2+x B 4+y O 7+z , the above Li 1+x B 3+y O 5+z , Li 3+x B 11+y O 18+z Li 3+x B 7+y O 12+z At least one of the following.

[0176] Furthermore, LiBO5, Li2B7O 12 , LiB2O3(OH)H2O and Li4B8O 13 At least one of (OH)2(H2O)3 and the like is used as the lithium-containing oxide.

[0177] In the solid electrolyte (I), the lithium-containing oxide is in an amorphous state. That is, the lithium-containing oxide in the solid electrolyte (I) is also in a desired amorphous state so that the solid electrolyte (I) is in the above-mentioned amorphous state.

[0178] Among them, the lithium-containing oxide is preferably lithium tetraborate in an amorphous state.

[0179] -Lithium salts-

[0180] The lithium salt constituting the solid electrolyte (I) used in the present invention is not particularly limited, and examples thereof include Li + and anions, preferably Li + and an organic anion, more preferably a salt composed of Li + And salts composed of organic anions having halogen atoms.

[0181] The lithium salt constituting the solid electrolyte (I) used in the present invention preferably contains two or more specific elements selected from the group consisting of elements of Group 3 of the periodic table, elements of Group 4 of the periodic table, elements of Group 13 of the periodic table, elements of Group 14 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table and H.

[0182] As the lithium salt constituting the solid electrolyte (I) used in the present invention, for example, a compound represented by the formula (1) is preferred.

[0183] Formula (1) LiN(R f1 SO2)(R f2 SO2)

[0184] R f1 and Rf2 Each independently represents a halogen atom or a perfluoroalkyl group.

[0185] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.

[0186] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.

[0187] The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is not limited to the compound represented by the above formula (1). The lithium salt that can be contained in the solid electrolyte (I) used in the present invention is exemplified below.

[0188] (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6 and LiSbF6; perhalide salts such as LiClO4, LiBrO4 and LiIO4; inorganic chloride salts such as LiAlCl4.

[0189] (L-2) Fluorine-containing organic lithium salts: perfluoroalkyl sulfonates such as LiCF3SO3; fluorosulfonyl imide salts or perfluoroalkyl sulfonyl imide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2 (also recorded as Li(FSO2)2N in this specification) and LiN(CF3SO2)(C4F9SO2); perfluoroalkyl sulfonyl methyl salts such as LiC(CF3SO2)3; fluoroalkyl fluorophosphates (preferably perfluoroalkyl fluorophosphates) such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2] and Li[PF3(CF2CF2CF2CF3)3].

[0190] (L-3) Oxalate borate: lithium bis(oxalato)borate and lithium difluorooxalatoborate.

[0191] In addition to the above, LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li2CO3, CH3COOLi, LiAsF6, LiSbF6, LiAlCl4 and LiB(C6H5)4 can also be mentioned.

[0192] Among them, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f1 SO2)、LiN(R f1 SO2)2, LiN(FSO2)2 or LiN(R f1 SO2)(R f2 SO2), more preferably LiPF6, LiBF4, LiN(R f1 SO2)2, LiN(FSO2)2 or LiN(R f1 SO2)(R f2 SO2). In these examples, R f1 and R f2 Each independently represents a perfluoroalkyl group and has preferably 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms, and further preferably 1 or 2. Furthermore, LiNO 3 and 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonylimide lithium are also preferred as the lithium salt.

[0193] (Elemental composition of solid electrolyte (I))

[0194] Regarding the solid electrolyte (I), the composition of the components is described based on the compound constituting the solid electrolyte (I). Next, the solid electrolyte (I) is described from the perspective of the preferred elemental composition. That is, in one embodiment of the secondary battery of the present invention, regarding the solid electrolyte (I), having "lithium-containing oxide" and "lithium salt" is not a specific matter, but can be determined by the elemental composition, for example, as follows.

[0195] The solid electrolyte (I) used in the present invention preferably has a molar amount of Li of 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and even more preferably 2.00 to 3.00) when the molar amount of B in the solid electrolyte (I) is 4.00. Furthermore, the molar amount of O is preferably 6.23 to 25.00 (preferably 6.50 to 23.00, more preferably 8.00 to 23.00, even more preferably 10.00 to 23.00, and even more preferably 10.00 to 18.00) when the molar amount of B in the solid electrolyte (I) is 4.00. Furthermore, the molar amounts of elements other than B, other than Li, and other than O are preferably 0.001 to 10.00 (preferably 0.001 to 6.00, and even more preferably 0.01 to 5.00), respectively.

[0196] The content of each element is determined by conventional elemental analysis. As a method of elemental analysis, for example, Li and B are analyzed by ICP-OES (Inductively coupled plasma optical emission spectrometry), N and the like are analyzed by an inert gas fusion method, and for example, F and S are analyzed by combustion ion chromatography. For O, the analysis masses of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Taking into account the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.

[0197] Based on the content of each element calculated by elemental analysis, the molar amounts of Li, O, and other elements when the molar amount of B is set to 4.00 were calculated.

[0198] In a preferred embodiment of the solid electrolyte (I), the solid electrolyte (I) contains, in addition to Li, B and O, one or more elements (E) selected from the group consisting of elements of Group 4, Group 15, Group 16, Group 17, Si, C, Sc and Y, more preferably two or more. Among them, it is preferred to contain one or more elements (E) selected from F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, preferably two or more.

[0199] Examples of the Group 4 elements of the periodic table include Ti, Zr, Hf and Rf. Examples of the Group 15 elements of the periodic table include N, P, As, Sb, Bi and Mc. Examples of the Group 16 elements of the periodic table include S, Se, Te, Po and Lv. Examples of the Group 17 elements of the periodic table include F, Cl, Br, I, At and Ts.

[0200] The number of the element (E) contained in the solid electrolyte (I) may be 3 or more, preferably 2 to 5, and more preferably 2 to 4.

[0201] The second embodiment of the solid electrolyte (I) preferably contains two or more elements (E) selected from F, S, N, P and C, more preferably contains two or more elements (E) selected from F, S, C and N, and further preferably contains three elements (E) of F, S and N.

[0202] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.49. That is, when the molar content of B is set to 4.00, the relative value of the molar content of Li is preferably 1.58 to 3.49. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of Li, the molar amount of Li is preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00.

[0203] In the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.23 to 25.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of O is preferably 6.23 to 25.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of O, the molar amount of O is preferably 6.50 to 23.00, more preferably 8.00 to 23.00, more preferably 10.00 to 23.00, and further preferably 10.00 to 18.00.

[0204] In a solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 10.00. That is, when the molar content of B is set to 4.00, the relative value of the molar content of each element (E) is preferably 0.001 to 10.00. Among them, when the molar amount of B in the solid electrolyte (I) is set to 4.00 to represent the molar amount of the element (E), the molar amount of each element (E) is preferably 0.001 to 6.00, and more preferably 0.01 to 5.00.

[0205] As one of the preferred aspects of the elemental composition of the solid electrolyte (I) containing one or more (preferably two or more) of the above-mentioned element (E), it can be mentioned that when Li, B, O, F, S and N are contained and the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and further preferably 2.00 to 3.00), the molar amount of O is 6.23 to 25.00 (preferably The molar amount of F is 0.001-10.00 (preferably 0.01-10.00), the molar amount of S is 0.001-2.00 (preferably 0.01-2.00), and the molar amount of N is 0.001-1.00 (preferably 0.005-1.00) of the solid electrolyte.

[0206] The solid electrolyte (I) used in the present invention is the above-mentioned amorphous solid electrolyte. As a result, it is preferred that the solid electrolyte (I) exhibits the following characteristics in addition to the above-mentioned X-ray diffraction characteristics.

[0207] (Solid State 7 Li-NMR spectral characteristics)

[0208] Regarding the solid electrolyte (I), the solid electrolyte (I) was solidified at 20°C and 120°C. 7 The full width at half maximum ratio calculated from the spectrum obtained by Li-NMR measurement by the method described below is preferably 50% or less, more preferably 40% or less, and further preferably 35% or less. The lower limit is not particularly limited, but is often 10% or more.

[0209] The above-mentioned half-peak full width ratio is obtained by the following calculation: The solid electrolyte (I) is solidified at 20°C and 120°C respectively. 7Li-NMR measurement, and after obtaining the half-maximum width (full width at half maximum 1) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 20°C and the half-maximum width (full width at half maximum 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained in the measurement at 120°C, the percentage of the ratio of the half-maximum width 2 to the half-maximum width 1 is calculated {(full width at half maximum 2 / full width at half maximum 1) × 100}. The full width at half maximum (FWHM) of the peak refers to the width (ppm) at the 1 / 2 point (H / 2) of the height (H) of the peak.

[0210] Below, use Figure 4 The above characteristics are explained below. Figure 4 In the figure, the solid electrolyte (I) is prepared at 20°C or 120°C. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 4 The solid line spectrum shown on the lower side is the solid state spectrum at 20°C. 7 The spectrum obtained during Li-NMR measurement is Figure 4 The dotted spectrum shown on the upper side is a spectrum obtained by solid-state heating at 120°C. 7 Spectra obtained during Li-NMR measurement.

[0211] Generally speaking, in solid 7 In Li-NMR measurement, Li + In case of high mobility, the peak obtained is sharper. Figure 4 In the manner shown, when comparing the spectrum at 20°C with the spectrum at 120°C, the spectrum at 120°C becomes sharper. Figure 4 In the embodiment shown, it is shown that Li + It is believed that the solid electrolyte (I) is prone to plastic deformation due to the defective structure as described above, and Li + Excellent jumping performance.

[0212] For reference, regarding ordinary lithium tetraborate crystals, solid-state 7 During Li-NMR measurement, Figure 5 The spectrum measured at 20°C is shown by the solid line at the bottom of Figure 5 The spectra measured at 120° C. indicated by the dotted line shown above tend to have substantially the same shape. That is, in the lithium tetraborate crystal, there are no Li defects or the like, and as a result, the elastic modulus is high and plastic deformation is not easily caused.

[0213] The above solid 7 Li-NMR measurement conditions are as follows.

[0214] The measurement was performed using a 4 mm HX CP-MAS probe by a single pulse method with a 90° pulse width of 3.2 μs, an observation frequency of 155.546 MHz, an observation width of 1397.6 ppm, a repetition time of 15 seconds, a cumulative integration of 1 time, and a MAS rotation speed of 0 Hz.

[0215] Furthermore, the solid electrolyte (I) used in the present invention is preferably as follows: 7 When the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is subjected to waveform separation, there is a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the above-mentioned area intensity is more preferably 2% or more, more preferably 5% or more, further preferably 10% or more, and further preferably 15% or more. In the embodiment of the present invention wherein the solid electrolyte (I) contains water, the solid electrolyte (I) 7 The Li-NMR spectrum characteristics tend to be as described above. The upper limit of the ratio of the area intensity is not particularly limited, but is often 50% or less.

[0216] Below, use Figure 6 and Figure 7 The above characteristics are described.

[0217] exist Figure 6 The solid electrolyte (I) is shown in FIG. 7 An example of a spectrum obtained during Li-NMR measurement. Figure 6 As shown, a peak (corresponding to the first peak) is observed in the solid electrolyte (I) in the range of -100 to +100 ppm, and in the first peak, a small peak surrounded by a dotted line is observed near the chemical shift of 0 ppm. + When the mobility is high, a sharp peak can be observed, thus producing its influence.

[0218] Then, in Figure 7 , a diagram showing the separation of the first peak waveform is shown. Figure 7 As shown, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dotted line. The second peak is a peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of less than 5 ppm.

[0219] The solid electrolyte (I) is preferably composed of Figure 7 The solid line represents the area intensity of the second peak relative to that of Figure 6 The ratio of the area intensity of the first peak (the peak before the waveform separation) {(area intensity of the second peak / area intensity of the first peak)×100} represented is within the above range.

[0220] As a method of waveform separation, a method using known software can be mentioned. As software, for example, Igor Pro, a graphics processing software of WaveMetrics, Inc. can be mentioned.

[0221] (Raman spectroscopy characteristics)

[0222] Regarding the solid electrolyte (I), in the Raman spectrum of the solid electrolyte (I), 600 to 850 cm -1 In the wave number region, the coefficient of determination obtained by linear regression analysis by the least square method is preferably 0.9400 or more, more preferably 0.9600 or more, and also preferably 0.9800 or more. The upper limit is not particularly limited, but is usually 1.0000 or less.

[0223] refer to Figure 8 , the above Raman spectral characteristics are explained.

[0224] First, a Raman spectrum of the solid electrolyte (I) is obtained. As a method for measuring Raman spectra, Raman imaging is implemented. Raman imaging refers to microscopic spectroscopy combined with microscopy in Raman spectroscopy. Specifically, it is a method of detecting measurement light containing Raman scattered light by scanning excitation light on a sample, and visualizing the distribution of components based on the intensity of the measurement light.

[0225] The measurement conditions for Raman imaging are set as follows: at 27°C and in the atmosphere, the excitation light is 532nm, the objective lens is 100 times, the point scanning is in the mapping mode, the step size is 1μm, the exposure time for each point is 1 second, the accumulation and integration times are 1 time, and the measurement range is 70μm×50μm.

[0226] Furthermore, the Raman spectrum data is subjected to principal component analysis (PCA) processing to remove noise. Specifically, in the principal component analysis processing, the spectrum is reorganized using components having an autocorrelation coefficient of 0.6 or more.

[0227] exist Figure 8 An example of the Raman spectrum of the solid electrolyte (I) is shown in FIG. Figure 8 In the graph shown, the vertical axis represents the Raman intensity and the horizontal axis represents the Raman shift. Figure 8 The Raman spectrum shown is 600-850 cm -1 The coefficient of determination (R 2 ). That is, in Figure 8 The Raman spectrum of 600-850 cm -1 In the wave number region, the regression line is obtained by the least square method ( Figure 8 The bold line in the figure is used to calculate the coefficient of determination R of the regression line. 2 In addition, the coefficient of determination takes a value between 0 (no linear correlation) and 1 (complete linear correlation of the measured values) depending on the linear correlation of the measured values.

[0228] In solid electrolyte (I), such as Figure 8 As shown, at 600-850cm -1 In the wavenumber region, almost no peak is observed, and as a result, a high determination coefficient is shown.

[0229] In addition, the above determination coefficient R 2 It is equivalent to the square of the correlation coefficient (Pearson product-moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 The calculation is performed by the following formula: wherein x1 and y1 represent the wave number in the Raman spectrum and the Raman intensity corresponding to the wave number, x2 represents the (arithmetic) average of the wave number, and y2 represents the (arithmetic) average of the Raman intensity.

[0230] [Formula 8]

[0231]

[0232] On the other hand, for reference, Fig. 9 The Raman spectrum of a typical lithium tetraborate crystal is shown in FIG. Fig. 9 As shown, in the case of a conventional lithium tetraborate crystal, the wavelengths of 716 to 726 cm-1 are derived from its structure. -1 and 771~785cm -1 In the wave number region of 600-850 cm -1 In the wave number region, when the coefficient of determination was calculated by linear regression analysis using the least squares method, the coefficient of determination was less than 0.9400.

[0233] That is, when the determination coefficient is 0.9400 or more, it means that the solid electrolyte (I) contains almost no crystal structure. Therefore, as a result, it is considered that the solid electrolyte (I) has the characteristics of being easy to plastically deform and Li + Excellent jumping properties.

[0234] (Infrared absorption spectrum characteristics)

[0235] In the infrared absorption spectrum of solid electrolyte (I), the -1The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wave number region (between 3000 and 3500 cm -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 The maximum absorption intensity in the wave number region of the wavelength region is preferably 1 / 5 or more (0.2 or more). Among them, the above ratio is preferably 3 / 10 or more, more preferably 2 / 5 or more. The upper limit is not particularly limited, but is preferably 1 or less.

[0236] In the infrared absorption spectrum, the range of 3000 to 3500 cm -1 The OH stretching vibration mode is observed in the wave number region of 800-1600 cm -1 The BO stretching vibration mode is observed in the wave number region of . From the solid electrolyte (I), it is observed that the absorption intensity derived from the OH stretching vibration mode is strong, which shows that a large number of OH groups or a large amount of water are contained. In this solid electrolyte (I), lithium ions become easy to move, and as a result, the ion conductivity tends to be improved.

[0237] In addition, at 800-1600cm -1 In the wave number region, vibration modes originating from lithium salts can also be observed.

[0238] The infrared absorption spectrum measurement conditions can be set as follows.

[0239] Objective lens: 32x Cassegrain (NA0.65), Detector: MCT-A, Measuring range: 650~4000cm -1 , Resolution: 4cm -1 , Sample cell: Use diamond cell for measurement.

[0240] The infrared absorption spectrum obtained was corrected to remove signals from water and CO 2 in the atmosphere, and the background was offset corrected so that the absorption intensity became 0. After vacuum drying at 40° C. for 2 hours, the spectrum was measured in the atmosphere.

[0241] The ion conductivity (27°C) of the solid electrolyte (I) is not particularly limited, but is preferably 1.0×10 -5 S / cm or more, more preferably 1.0×10 -4 S / cm or more, more preferably 1.0×10 -3 S / cm or more, particularly preferably 3.0×10 -3 S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.

[0242] Furthermore, the solid electrolyte (I) also preferably exhibits the following characteristics or properties.

[0243] (Mass reduction rate)

[0244] The mass reduction rate of the solid electrolyte (I) when heated to 800°C is preferably 20 to 40% by mass, more preferably 25 to 35% by mass. The mass reduction caused by the above heating is considered to be at least the removal of water contained in the solid electrolyte (I). By containing such water, the solid electrolyte (I) can further improve the conductivity of lithium ions.

[0245] In the above-mentioned heating treatment, heating is performed at a temperature increase rate of 20°C / second within a range of 25°C to 800°C. When measuring the mass reduction, a known thermogravimetric differential thermal analysis (TG-DTA) device can be used. The above-mentioned mass reduction rate is calculated as follows:

[0246] {(mass at 25°C - mass at 800°C) / mass at 25°C}×100.

[0247] When measuring the mass reduction rate, the solid electrolyte (I) was previously vacuum dried at 40° C. for 2 hours. The mass reduction rate was measured in the atmosphere.

[0248] The solid electrolyte layer constituting the secondary battery of the present invention may contain other components in addition to the solid electrolyte (I).

[0249] For example, the solid electrolyte layer can include a binder composed of an organic polymer. The organic polymer constituting the binder can be in a particle form or a non-particle form. By including the binder, cracks can be more reliably prevented from occurring in the solid electrolyte layer or the electrode layer.

[0250] Furthermore, the solid electrolyte layer may include other solid electrolytes other than the solid electrolyte (I). Other solid electrolytes refer to solid electrolytes that enable lithium ions to move inside them. As solid electrolytes, inorganic solid electrolytes are preferred. As other solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes and hydride solid electrolytes can be cited. If safety is taken into account, at least one of oxide solid electrolytes, halide solid electrolytes and hydride solid electrolytes is preferred, and oxide solid electrolytes are more preferred.

[0251] In the solid electrolyte layer, the content of the solid electrolyte (I) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, also preferably 80 mass % or more, and even preferably 90 mass %.

[0252] The thickness of the solid electrolyte layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 1000 μm, preferably 50 to 400 μm.

[0253] <Positive electrode layer>

[0254] The positive electrode layer is usually composed of a positive electrode collector and a positive electrode active material layer, but when the positive electrode collector also functions as a positive electrode active material layer (in other words, when the positive electrode active material layer also functions as a positive electrode collector), it is not necessary to be composed of the two layers of the positive electrode collector and the positive electrode active material layer, and can be a single-layer structure. In addition, the positive electrode active material layer usually contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the positive electrode active material, but may not contain a solid electrolyte. The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, also preferably 80% by mass or more, and also preferably 90% by mass.

[0255] When the positive electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of attaching importance to flexibility, a sulfide-based solid electrolyte can be used, and from the viewpoint of attaching importance to higher safety, an oxide-based solid electrolyte can be used.

[0256] From the viewpoint of achieving both flexibility and safety at a high level, it is preferred to use the above-mentioned solid electrolyte (I). In this way, the solid electrolyte (I) can also act as a binder to the solid particles contained in the positive electrode layer, thereby enabling the positive electrode layer to have higher flexibility.

[0257] The positive electrode active material used in the positive electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the positive electrode active material will be described below.

[0258] (Positive electrode active material)

[0259] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, preferably a transition metal oxide, more preferably a transition metal oxide containing a transition metal element Ma (one or more elements selected from Co, Ni, Fe, Mn, Cu and V). In addition, the element Mb (metal elements of the 1st (Ia) group of the periodic table other than lithium, elements of the 2nd (IIa) group, Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P and B, etc.) can be mixed in the transition metal oxide. As a mixed amount, it is preferably 0 to 30 mol% relative to the amount of the transition metal element Ma (100 mol%). More preferably, the material is synthesized by mixing in a manner such that the molar ratio of Li / Ma is 0.3 to 2.2.

[0260] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) transition metal phosphate compounds containing lithium, (MD) transition metal halophosphate compounds containing lithium, and (ME) transition metal silicate compounds containing lithium. Among them, (MA) transition metal oxides having a layered rock salt structure are preferred, and LiCoO2 or LiNi2O3 are more preferred. 1 / 3 Co 1 / 3 Mn 1 / 3 O2.

[0261] Examples of the transition metal oxide (MA) having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNiO2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).

[0262] Examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiNi 0.5 Mn 1.5 O4([LNMO]), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.

[0263] As (MC) transition metal phosphate compounds containing lithium, for example, there can be mentioned olivine-type iron phosphate salts such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphate iron salts such as Li2CoP2O7(LCP) and LiFeP2O7, cobalt phosphate salts such as LiCoPO4, and monoclinic NASICON-type vanadium phosphate salts such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0264] Examples of the lithium-containing transition metal halophosphate compound (MD) include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0265] Examples of the (ME) lithium-containing transition metal silicate compound include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .

[0266] The shape of the positive electrode active material is not particularly limited, and is usually in the form of particles. The volume average particle size of the positive electrode active material is not particularly limited, and is preferably 0.1 to 50 μm, for example. The volume average particle size of the positive electrode active material particles can be determined in the same manner as the volume average particle size of the negative electrode active material described later.

[0267] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.

[0268] The positive electrode active material may be surface-coated with a surface coating agent, sulfur or phosphorus, which will be described later, in the same manner as the negative electrode active material, which will be described later, or with active light.

[0269] The positive electrode active material may be used alone or in combination of two or more.

[0270] (Positive electrode collector)

[0271] The current collector constituting the positive electrode layer is an electron conductor and is usually in the form of a thin film sheet.

[0272] As the constituent material of the positive electrode collector, aluminum, aluminum alloy, stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. In addition, as the positive electrode collector, a positive electrode collector (forming a thin film) treated with carbon, nickel, titanium or silver on the surface of aluminum or stainless steel can also be cited.

[0273] The thickness of the positive electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm.

[0274] The thickness of the positive electrode current collector constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm.

[0275] <Negative electrode layer>

[0276] The negative electrode layer is usually composed of a negative electrode collector and a negative electrode active material layer, but when the negative electrode collector also functions as a negative electrode active material layer (in other words, when the negative electrode active material layer also functions as a negative electrode collector), it is not necessary to be composed of the two layers of the negative electrode collector and the negative electrode active material layer, and can be a single-layer structure. In addition, the negative electrode active material layer usually contains a solid electrolyte (preferably an inorganic solid electrolyte) together with the negative electrode active material, but may not contain a solid electrolyte.

[0277] The content of the negative electrode active material in the negative electrode active material layer is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, also preferably 80 mass % or more, and even preferably 90 mass %.

[0278] When the negative electrode active material layer contains a solid electrolyte, the type of the solid electrolyte is not particularly limited. From the viewpoint of attaching importance to flexibility, a sulfide-based solid electrolyte can be used, and from the viewpoint of attaching importance to higher safety, an oxide-based solid electrolyte can be used.

[0279] From the viewpoint of achieving both flexibility and safety at a high level, it is preferred to use the above-mentioned solid electrolyte (I). In this way, the solid electrolyte (I) can also act as a binder for the solid particles contained in the negative electrode layer, thereby making the negative electrode layer have higher flexibility.

[0280] The negative electrode active material used in the negative electrode layer itself can be widely used from those that can be used in ordinary lithium ion secondary batteries. Preferred embodiments of the negative electrode active material will be described below.

[0281] (Negative electrode active material)

[0282] The negative electrode active material is preferably a negative electrode active material that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metal or semimetal elements, lithium monomers, lithium alloys, and negative electrode active materials that can form alloys with lithium.

[0283] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon, for example, carbonaceous materials made of various synthetic resins such as calcined petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and PAN (polyacrylonitrile) resin or furfuryl alcohol resin.

[0284] In addition, various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as intermediate phase microspheres, graphite whiskers, and flat graphite can also be cited.

[0285] These carbonaceous materials can be further divided into hardly graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials according to the degree of graphitization.

[0286] Furthermore, the carbonaceous material preferably has the interplanar spacing, density or crystallite size described in Japanese Patent Laid-Open No. 62-022066, Japanese Patent Laid-Open No. 2-006856 and Japanese Patent Laid-Open No. 3-045473. The carbonaceous material need not be a single material, and a mixture of natural graphite and artificial graphite described in Japanese Patent Laid-Open No. 5-090844 and graphite with a coating layer described in Japanese Patent Laid-Open No. 6-004516 can also be used.

[0287] As the carbonaceous material, hard carbon or graphite is preferred, and graphite is more preferred.

[0288] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can occlude and release lithium, and examples thereof include oxides of metal elements (metal oxides), composite oxides of metal elements, composite oxides of metal elements and semi-metal elements, and oxides of semi-metal elements (semi-metal oxides). In addition, composite oxides of metal elements and composite oxides of metal elements and semi-metal elements are collectively referred to as metal composite oxides.

[0289] As these oxides, amorphous oxides are preferred, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred.

[0290] In the present invention, semi-metallic elements refer to elements showing properties between metal elements and non-metallic elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and also include three elements of selenium, polonium and astatine.

[0291] Furthermore, amorphous means that, by X-ray diffraction using CuKα rays, a broad scattering band having a vertex in a region of 20 to 40° in 2θ values ​​may also have crystalline diffraction lines. It is preferred that the strongest intensity of the crystalline diffraction lines seen in a region of 40 to 70° in 2θ values ​​is 100 times or less, more preferably 5 times or less, and further preferably a diffraction line having no crystalline diffraction line intensity at the vertex of the broad scattering band seen in a region of 20 to 40° in 2θ values.

[0292] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides consisting of a single element or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (for example, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi) are further preferred.

[0293] As amorphous oxides and chalcogenides, preferred are Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5.

[0294] As the negative electrode active material that can be used together with the amorphous oxide negative electrode active material centered on Sn, Si or Ge, carbonaceous materials that can occlude and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, or negative electrode active materials that can alloy with lithium are preferred.

[0295] From the viewpoint of high current density charge and discharge characteristics, the oxide of a metal element or a semi-metal element (particularly a metal (complex) oxide) and the above-mentioned chalcogenide preferably contain at least one of titanium and lithium as a constituent component.

[0296] Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above-mentioned metal oxides, the above-mentioned metal composite oxides or the above-mentioned chalcogenides. More specifically, Li2SnO2 is included.

[0297] The negative electrode active material (e.g., metal oxide) also preferably contains titanium (titanium oxide). Specifically, since the volume change when absorbing and releasing lithium ions is small, the rapid charge and discharge characteristics are excellent. From the perspective of being able to increase the life of the all-solid-state lithium ion secondary battery that suppresses electrode degradation, Li4Ti5O is preferred. 12 (lithium titanate [LTO]).

[0298] The lithium alloy used as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as a negative electrode active material for all-solid-state lithium ion secondary batteries, and examples thereof include lithium aluminum alloys.

[0299] The negative electrode active material capable of alloying with lithium is not particularly limited as long as it is a material commonly used as the negative electrode active material of an all-solid-state lithium-ion secondary battery. Examples of the negative electrode active material include negative electrode active materials (alloys) containing silicon or tin elements, and various metals such as Al and In. Preferred is a negative electrode active material containing silicon (active material containing silicon element) that can achieve a higher battery capacity, and more preferably an active material containing silicon element with a silicon element content of 50 mol% or more of all constituent elements.

[0300] Generally, a negative electrode containing these negative electrode active materials (for example, a Si negative electrode containing an active material containing silicon element, a Sn negative electrode containing an active material containing tin element) can occlude more Li ions compared to a carbon negative electrode (such as graphite and acetylene black). That is, the occluding amount of Li ions per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.

[0301] Examples of the active material containing silicon element include silicon materials such as Si and SiOx (0 < x ≤ 1), and further include silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, or lanthanum (for example, LaSi2, VSi2, La-Si, Gd-Si, and Ni-Si) or organized active materials (for example, LaSi2 / Si). In addition, active materials containing silicon element and tin element such as SnSiO3 and SnSiS3 can be cited. Regarding SiOx, it can be used as a negative electrode active material (semi-metal oxide) itself, and since Si is generated by the operation of an all-solid-state lithium-ion secondary battery, it can be used as a negative electrode active material (its precursor material) capable of alloying with lithium.

[0302] Examples of the negative electrode active material having a tin element include those containing Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned active materials containing silicon element and tin element.

[0303] From the viewpoint of battery capacity, as the negative electrode active material, a negative electrode active material capable of alloying with lithium is preferred, more preferably the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element), and further preferably silicon (Si) or silicon-containing alloy.

[0304] As the negative electrode active material, it is also preferable to use a titanium niobium composite oxide. The titanium niobium composite oxide has a high theoretical volume capacity density, and it can be expected to have a long life and also be capable of fast charging. Examples of the titanium niobium composite oxide include TiNb2O7 and the like.

[0305] The shape of the negative electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.

[0306] The volume average particle size is measured by the following procedure.

[0307] Use water (heptane in the case of unstable substances in water) to dilute the negative electrode active material in a 20 mL sample bottle to prepare a 1% dispersion. The diluted dispersion sample was irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, 50 data readings were performed using a measuring quartz cell at a temperature of 25°C to obtain the volume average particle size. For other detailed conditions, refer to JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.

[0308] The negative electrode active material may be used alone or in combination of two or more.

[0309] The surface of the negative electrode active material may also be coated with another metal oxide.

[0310] As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be cited. Specifically, titanate spinel, tantalum oxides, niobium oxides and lithium niobate compounds can be cited, for example, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3 and Li3AlF6.

[0311] Furthermore, the surface of the electrode including the negative electrode active material may be surface-treated with sulfur or phosphorus.

[0312] Furthermore, the surface of the negative electrode active material particles may be subjected to a surface treatment using active light or active gas (for example, plasma) before or after the surface is coated.

[0313] (Negative electrode current collector)

[0314] The current collector constituting the negative electrode layer is an electron conductor and is usually in the form of a thin film sheet.

[0315] As the constituent material of the negative electrode collector, aluminum, copper, copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode collector, a negative electrode collector treated with carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.

[0316] The thickness of the negative electrode active material layer constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 5 to 500 μm, preferably 20 to 200 μm.

[0317] The thickness of the negative electrode current collector constituting the secondary battery of the present invention is not particularly limited, and can be, for example, 10 to 100 μm, preferably 10 to 50 μm.

[0318] The positive electrode layer and the negative electrode layer may contain components other than the solid electrolyte and the active material (other components) in their active material layers. For example, a conductive auxiliary agent may be contained.

[0319] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.

[0320] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atoms, such as metal powder or metal fiber, can be used.

[0321] A conductive aid is an aid that does not insert or release Li during battery charge and discharge and does not function as an active material. Therefore, among conductive aids, substances that function as active materials in the active material layer during battery charge and discharge are also classified as active materials rather than conductive aids. Whether or not a conductive aid functions as an active material during battery charge and discharge is not unique, but is determined by the combination with the active material.

[0322] As other components, the above-mentioned binder and lithium salt can be mentioned.

[0323] <Manufacturing of all-solid-state lithium-ion secondary batteries>

[0324] The secondary battery of the present invention uses a solid electrolyte (I) at least in the solid electrolyte layer. In addition, it can be manufactured with reference to the usual method for manufacturing an all-solid-state secondary battery. In addition, in the obtained secondary battery, in order to reduce the moisture content of the laminate composed of the positive active material layer, the solid electrolyte layer and the negative active material layer to the level specified in the present invention, it is preferred that in the manufacture of the secondary battery of the present invention, a solid electrolyte (I) is used to form a laminate comprising a positive active material layer, a solid electrolyte layer and a negative active material layer, and then a vacuum drying process described later is performed. With regard to the method for manufacturing the secondary battery of the present invention, a preferred embodiment is described.

[0325] The manufacturing method of the secondary battery of the present invention includes the step of obtaining a laminated body formed by sequentially configuring a positive electrode layer, a solid electrolyte layer and a negative electrode layer. In addition, in order to set the water amount of the laminated body composed of a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer to the amount specified in the present invention, it is preferred that in the manufacture of the secondary battery of the present invention, a process of drying the laminated body comprising a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer is included. The drying process can be performed at any stage after the laminated body is formed. In order to more reliably set the water amount to the amount specified in the present invention, it is preferred that at least the laminated body formed by sequentially configuring a positive electrode layer, a solid electrolyte layer and a negative electrode layer is dried in a state in which the laminated body is configured in a battery cell. There is no particular limitation on the drying method, for example, a dryer can be used, or vacuum drying (preferably freeze vacuum drying) can be performed, or heat treatment can be performed, and the water content of the laminated body composed of a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer can be reduced to within the range specified in the present invention.

[0326] The secondary battery of the present invention is preferably a secondary battery formed by sealing the laminate formed by sequentially configuring the positive electrode layer, the solid electrolyte layer and the negative electrode layer. By sealing, it is possible to more reliably prevent moisture from mixing into the solid electrolyte layer after the above-mentioned drying process, thereby further improving the cycle characteristics. The sealing method is not particularly limited, as long as the mixing of moisture (atmosphere) can be completely prevented or suppressed. For example, a method of sealing the laminate by closing the cover of the shell (battery cell) storing the laminate formed by sequentially configuring the positive electrode layer, the solid electrolyte layer and the negative electrode layer through a gasket such as an O-ring, etc.

[0327] Furthermore, there is no particular limitation on the method for forming a laminated body in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are sequentially arranged. For example, a positive electrode forming composition (slurry) containing a positive electrode active material is applied to a metal foil as a positive electrode collector to form a positive electrode active material layer, and then a solid electrolyte layer forming dispersion (slurry) containing a solid electrolyte is applied to the positive electrode active material layer to form a solid electrolyte layer, and further, a negative electrode forming composition (slurry) containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector (metal foil) is overlapped on the negative electrode active material layer. The whole can be dried as needed and subjected to a pressure treatment to obtain a product such as Figure 1 The all-solid-state lithium-ion secondary battery shown.

[0328] Furthermore, an all-solid-state lithium ion secondary battery can be manufactured by reversing the formation method of each layer, forming a negative electrode active material layer, a solid electrolyte layer and a positive electrode active material layer on a negative electrode collector, and pressurizing the entirety as necessary.

[0329] As another method, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer may be separately prepared, stacked, and dried and pressed as necessary to produce an all-solid-state lithium ion secondary battery.

[0330] In this case, in the formation of each layer, a support such as a nonwoven fabric may be disposed as necessary so that each layer becomes a self-supporting film.

[0331] In addition, the manufacturing method of the secondary battery of the present invention is not limited to the manufacturing method described above as long as the secondary battery specified in the present invention can be obtained.

[0332] In the manufacture of the secondary battery of the present invention, even if a sulfide-based solid electrolyte is not used as the solid electrolyte, the formation of a layer that suppresses the interface resistance between solid particles or between layers can be achieved through the action of the above-mentioned oxide-based solid electrolyte (I) that can easily undergo plastic deformation under pressure.

[0333] The solid electrolyte (I) itself is soft and plastically deformable, and acts like a binder to help improve the adhesion between solid particles and between layers. Therefore, it is possible to form layers without using a binder such as an organic polymer.

[0334] The secondary battery of the present invention is preferably initialized after manufacture or before use. The initialization method is not particularly limited, and can be performed, for example, by performing initial charge and discharge under increased pressure and then releasing the pressure until the pressure condition is within the range when the secondary battery is used.

[0335] <Applications of all-solid-state lithium-ion secondary batteries>

[0336] The secondary battery of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game consoles, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.

[0337] The present invention will be described in further detail based on Examples, but the interpretation of the present invention is not limited to these Examples.

[0338] Example

[0339] [Reference Example 1]

[0340] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) were ball-milled under the following conditions: pot: yttria-stabilized zirconia (YSZ) (45 mL), grinding balls: YSZ (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder amount: 1 g, atmosphere: air, and ball mill processing time: 100 hours, thereby obtaining a micronized lithium-containing oxide (hereinafter also referred to as "micronized lithium-containing oxide").

[0341] 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added as a lithium salt to 1 g of the obtained lithium oxide-containing fine material (5% by mass relative to the lithium oxide-containing fine material), and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42% by mass, and ultrasonic dispersion was performed for 30 minutes. Then, the obtained dispersion was transferred to a glass petri dish and dried at 120°C for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Then, the obtained film was peeled off to obtain a powdery solid electrolyte (I)-1.

[0342] <Production and evaluation of solid electrolyte molded body>

[0343] The powdered solid electrolyte (I)-1 obtained above was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a solid electrolyte molded body (compressed powder body 1). The shape of the compressed powder body 1 was a cylinder with a diameter of 10 mm and a thickness of 0.5 to 1 mm. The ion conductivity of the compressed powder body 1 was measured and the ion conductivity of the compressed powder body 1 was 1.5×10 -4 S / cm, and 4.0×10 at 60°C -4 S / cm.

[0344] The ionic conductivity of the above-mentioned solid electrolyte (I)-1 was calculated by the following method: electrodes consisting of two In foils were arranged in a manner of clamping the powder compact 1, and the AC impedance between the two In electrodes was measured in the measurement frequency range of 1 Hz to 1 MHz at a measurement temperature of 27°C or 60°C and an applied voltage of 50 mV, and the arc diameter of the obtained Cole-Cole diagram (Nyquist diagram) was analyzed.

[0345] As described above, using CuKα rays, X-ray diffraction measurement of solid electrolyte (I)-1 was performed. The measurement conditions were set to 0.01° / step and 3° / minute. The results showed that the above-mentioned X-ray diffraction characteristics were satisfied, which showed that solid electrolyte (I)-1 was in an amorphous state.

[0346] The solid electrolyte (I)-1 obtained in the above was used and the solid electrolyte (I)-1 was measured by SPring-8L04B2 (accelerating voltage: 61.4 keV, wavelength: ) Total X-ray scattering measurements were performed. The samples were sealed in a 2 mm φ or 1 mm φ Kapton capillary and the experiment was performed. As described above, the obtained data were Fourier transformed to obtain the reduced two-body distribution function.

[0347] As a result of the analysis, it was confirmed that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, when r is In the range of , the peak G(r) shows more than 1.0, and the peak is located at The first peak and the peak G(r) show more than 1.0, and the peak is located at The second peak of

[0348] On the other hand, in solid electrolyte (I)-1, the peaks attributed to the BO distance and BB distance observed in ordinary lithium tetraborate crystals are maintained. Ordinary lithium tetraborate crystals have a structure (diborate structure) in which BO4 tetrahedrons and BO3 triangles exist in a 1:1 ratio, and it is inferred that in solid electrolyte (I)-1, its structure is maintained.

[0349] Solid electrolyte (I)-1 was prepared at 120 °C. 7 The full width at half maximum (FWHM 2) of the peak whose chemical shift appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement is relative to the solid electrolyte (I)-1 obtained above at 20°C. 7 The ratio of the full width at half maximum (FWHM 1) of the peak whose chemical shift appeared in the range of -100 to +100 ppm in the spectrum obtained in Li-NMR measurement {(FWHM 2 / FWHM 1)×100} was 33%.

[0350] Will be solid at 20℃ 7 When the waveform of the first peak appearing in the range of -100 to +100 ppm in the spectrum obtained during Li-NMR measurement is separated, a second peak having a chemical shift in the range of -3 to 3 ppm and a half-maximum width of less than 5 ppm is obtained, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 4%.

[0351] The solid electrolyte (I)-1 obtained in the above-mentioned manner was used and infrared absorption spectrum was measured under the above-mentioned conditions. In the infrared absorption spectrum obtained, the -1 The maximum absorption intensity in the wave number region is relatively large compared to that in the region of 800 to 1600 cm -1 The ratio of the maximum absorption intensity in the wavenumber region is 0.72.

[0352] In the Raman spectrum of the solid electrolyte (I)-1 obtained above, the -1 The coefficient of determination obtained by least squares linear regression analysis in the wavenumber region is 0.9974.

[0353] As described above, the mass reduction rate when the solid electrolyte (I)-1 was heated from 25°C to 800°C was 29.8%.

[0354] Regarding the analysis of each element in the obtained solid electrolyte (I)-1, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC), and regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Li salt, and regarding O, the analysis mass of the elements other than O was added and calculated as a difference from the total amount of powder. The results are shown in the following table.

[0355] [Reference Example 2]

[0356] 1 g of the lithium oxide-containing fine substance used in Reference Example 1 was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic dispersion was performed for 30 minutes. 0.05 g of LiFSI (chemical formula: Li(FSO2)2N) was added to the obtained dispersion as a lithium salt (5 mass % relative to the lithium oxide-containing fine substance), and ultrasonic dispersion was performed for 30 minutes.

[0357] The obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a solid electrolyte. Next, the obtained thin film was peeled off to obtain a powdered solid electrolyte (I)-2. Regarding the solid electrolyte (I)-2, various evaluations were performed in the same manner as in Reference Example 1 in the atmosphere. The results are summarized in the following table.

[0358] [Reference Example 3]

[0359] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), powdered Li2B4O7 (LBO powder) (manufactured by RARE METALLIC Co., Ltd.) was ball milled under the conditions of pot: YSZ (45 ml), grinding balls: YSZ (average particle size: 5 mm, weight: 70 g), rotation speed: 530 rpm (revolutions per minute), LBO powder amount: 4.2 g, atmosphere: air, and ball mill processing time: 100 hours to obtain a fine substance containing lithium oxide.

[0360] The obtained lithium oxide-containing fine substance was added to water so that the concentration of the fine substance became 42 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a dispersion liquid 1.

[0361] Next, 3.25 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 2 .

[0362] The obtained dispersion 1 and solution 2 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-3. The obtained powder was allowed to stand for a certain period of time in the atmosphere, and various evaluations were performed in the same manner as in Reference Example 1 using the solid electrolyte (I)-3 in the atmosphere. The results are summarized in the following table.

[0363] [Reference Example 4]

[0364] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 3 was obtained.

[0365] Next, 2.32 g of LiFSI (chemical formula: Li(FSO 2 ) 2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 4 .

[0366] The obtained dispersion 3 and solution 4 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-4. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-4 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0367] [Reference Example 5]

[0368] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 5 was obtained.

[0369] Next, 4.65 g of LiFSI (chemical formula: Li(FSO 2 ) 2 N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 6 .

[0370] The obtained dispersion 5 and solution 6 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-5. The obtained powder was immediately subjected to various evaluations in the same manner as in Reference Example 1 under the atmosphere. The results are summarized in the following table.

[0371] [Reference Example 6]

[0372] In the same manner as in the preparation of Dispersion Liquid 1 in Reference Example 3, Dispersion Liquid 7 was obtained.

[0373] Next, 7.13 g of LiTFSI (chemical formula: Li(F3CSO2)2N) as a lithium salt was added to water at a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 8.

[0374] The obtained dispersion 7 and solution 8 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-6. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-6 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0375] In Reference Example 6, the carbon content shown in Table 1 below was estimated from the analyzed mass of sulfur in consideration of the atomic weights of the lithium salt.

[0376] [Comparative Reference Example 1]

[0377] The elemental analysis of the LBO powder (Li2B4O7 crystals in powder form without ball milling) used in Reference Example 1 showed that the composition of the LBO powder obtained was Li 1.96 B 4.00 O 6.80 The LBO powder was compacted at 27° C. (room temperature) at an effective pressure of 220 MPa to obtain a comparative powder compact C1. The ion conductivity of the obtained powder compact C1 could not be detected.

[0378] Furthermore, in the same manner as in Reference Example 1, total X-ray scattering measurement was performed using LBO powder to obtain the reduced two-body distribution function G(r). Fig.10 In FIG. 5 , the reduced two-body distribution function G(r) obtained from total X-ray scattering measurements is shown.

[0379] The analysis results show that in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement of LBO powder, there is a peak located at The first peak (corresponding to the vicinity of BO) and the peak are located at The second peak of the BB (corresponding to the BB), the peak G (r) of the first peak and the second peak is greater than 1.0 (reference Fig.10 ). In addition, there is a peak located at and The absolute value of the peak G(r) of each peak obviously exceeds 1.0 (ref. Fig.10 ).

[0380] Furthermore, as described above, X-ray diffraction measurement was performed on the LBO powder. The measurement conditions were set to 0.01° / step and 3° / minute. Fig.11 , the X-ray diffraction pattern of the LBO powder of Comparative Reference Example 1 is shown. Fig.11 As shown, in the LBO powder used in comparative reference example 1, multiple small peaks of width were observed. More specifically, the strongest peak corresponding to the (1,1,2) plane was observed at a position with a 2θ value of 21.78°. As other major diffraction peaks, a peak corresponding to the (2,0,2) plane was shown at a position of 25.54°, a peak corresponding to the (2,1,3) plane was shown at a position of 33.58°, and a peak corresponding to the (3,1,2) plane was shown at a position of 34.62°, and the intensities of these three peaks were roughly the same. These peaks originate from the crystal components.

[0381] [Comparative Reference Example 2]

[0382] The result of elemental analysis of the fine material containing lithium oxide prepared in Reference Example 1 (the material obtained by ball milling powdered Li2B4O7 crystals) showed that the composition of the fine material containing lithium oxide was Li 1.94 B 4.00 O 6.80 .

[0383] Next, the lithium oxide-containing fine material was pressed at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a reference powder compact (powder compact R1). The ion conductivity of the obtained powder compact R1 at 27°C was 7.5×10 -9 S / cm, and 7.5×10 at 60°C -8 S / cm.

[0384] In the following table, as described above, in the reduced two-body distribution function G(r) obtained from the total X-ray scattering measurement, there is a peak located at r The first peak and the peak top in the range of r are If the peak G(r) of the first peak and the peak G(r) of the second peak show a value greater than 1.0, the "Short-range G(r)" column is set to "A", and all other cases are set to "B".

[0385] In Reference Examples 1 to 4 shown in the following table and Reference Examples 9 to 12 described later, the value of the peak top G(r) of the first peak was 1.2 or more.

[0386] Furthermore, in the above-mentioned reduced two-body distribution function G(r), when r is greater than and When the absolute value of G(r) in the following range is less than 1.0, the "Long-range G(r)" column in the following table is set to "A", and when the absolute value of G(r) does not satisfy less than 1.0, it is set to "B".

[0387] In addition, the result of the X-ray diffraction measurement using the above-mentioned CuKα ray is set as "A" when the above-mentioned X-ray diffraction characteristics are satisfied, and "B" when the above-mentioned X-ray diffraction characteristics are not satisfied. In addition, in Reference Examples 1 to 6 shown in the following table and Reference Examples 7 to 13 described later, in the X-ray diffraction spectrum, the first peak, the second peak, the third peak, and the fourth peak are not present, or the intensity ratio of at least one of the first peak, the second peak, the third peak, and the fourth peak is 2.0 or less.

[0388] In the following table, in the "Elemental Analysis" column, the composition of the solid electrolyte (I) obtained in each reference example and the lithium-containing oxide in each comparative reference example is expressed as a relative value with the B content being set to "4.00" and expressed in terms of the molar amount of each element.

[0389] In the following table, the “area intensity ratio” is the ratio of the above solid state 7 In the Li-NMR measurement, the ratio of the area intensity of the second peak to the area intensity of the first peak was measured, and the evaluation results were described based on the following criteria.

[0390] <Standards for the ratio of area strength>

[0391] A: When the area strength ratio is 15% or more

[0392] B: When the ratio of area strength is 0.5% or more and less than 15%

[0393] C: When the ratio of area intensity is less than 0.5%

[0394] In the following table, the "Maximum Absorption Intensity Ratio" column indicates whether the above infrared absorption spectrum characteristics are met. -1 The maximum absorption intensity in the wave number region of 800 to 1600 cm -1 When the maximum absorption intensity in the wave number region is greater than 0.20, it is represented as A, and when it is less than 0.20, it is represented as B.

[0395] In the following table, "-" means that the measured value is not shown.

[0396] [Table 1]

[0397]

[0398] [Table 2]

[0399]

[0400] As shown in the above table, it can be seen that the solid electrolytes (I)-1, (I)-2, (I)-3, (I)-4, (I)-5 and (I)-6 of Reference Examples 1 to 6 have excellent ion conductivity. In addition, according to the results of elemental analysis, it is confirmed that the content of Li in the solid electrolyte is higher in Reference Examples 3 to 6. In Reference Examples 3 to 6, an aqueous solution containing a mechanically milled lithium compound and an aqueous solution containing a lithium salt (method 3 in the above-mentioned step 2B) are mixed, and more lithium salts can be mixed. As a result, it is speculated that the amount of Li entering the solid electrolyte has increased. In addition, it can be seen that in Reference Examples 3, 4 and 5 using LiFSI as a lithium salt, the ion conductivity is further improved. It is speculated that this is because the increased Li contains Li with high mobility.

[0401] <Effect of water in solid electrolyte>

[0402] The solid electrolyte (I)-3 powder compact (granules) (10 mm φ, 0.9 mm t) obtained in Reference Example 3 was vacuum dried at 27°C under a constraint of 60 MPa, and the pressure change and ion conductivity relative to the vacuum drying time were investigated. In addition, the method for preparing the powder compact and the evaluation of ion conductivity were as described above, except that the In electrode was changed to a Ti electrode. The results are shown in Table 3.

[0403] [Table 3]

[0404]

[0405] The solid electrolyte (I)-3 of Reference Example 3 has a wavelength of 3000-3500 cm in the infrared absorption spectrum. -1 The OH stretching peak of the particles increases, so it is believed that a large amount of OH groups or water exists. In addition, regarding water, it is inferred that free water and bound water exist. In the above, the particles are first dried under conditions that are believed to volatilize from free water by vacuum drying, and then the particles are dried under strict drying conditions, so that the ion conductivity of each stage is evaluated.

[0406] As shown in the above table, the drying time was 5 minutes and the pressure was 200 Pa. It is considered that the free water was in a state of evaporation, but the ion conductivity showed 3.8×10 -3 S / cm, and the ionic conductivity showed 5.7×10 -4 S / cm. This result indicates that bound water in addition to free water exists and this contributes to ion conductivity.

[0407] [Reference Example 7]

[0408] In the same manner as in the preparation of the dispersion 1 in the above-mentioned Reference Example 3, a dispersion 9 having a concentration of 42% by mass of fine substances containing lithium oxide was obtained.

[0409] Next, 7.12 g of LiTFSI (chemical formula: Li(F 3 CSO 2 ) 2 N) as a lithium salt was added to water so as to have a concentration of 87 mass %, and ultrasonic treatment was performed for 60 minutes, thereby obtaining a solution 10 .

[0410] The obtained dispersion 9 and solution 10 were mixed and stirred for 60 minutes with a magnetic stirrer. Then, the obtained dispersion was vacuum dried at 40°C and 10Pa for 15 hours to obtain a powdered solid electrolyte (I)-7. The obtained powder was allowed to stand for a certain period of time under the atmosphere, and various evaluations were performed under the atmosphere using the solid electrolyte (I)-7 in the same manner as in Reference Example 1. The results are summarized in the following table.

[0411] [Reference Example 8]

[0412] Solid electrolyte (I)-8 was obtained in the same manner as Reference Example 7 except that the contents of water and LiTFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, and various evaluations were performed under air in the same manner as Reference Example 1. The results are summarized in the following table.

[0413] [Reference Examples 9 to 13]

[0414] Except that LiTFSI was changed to LiFSI and the contents of water and LiFSI in the obtained solid electrolyte (I) were changed to the amounts described in the following table, solid electrolytes (I)-9 to (I)-13 were obtained in the same manner as in Reference Example 7, and various evaluations were performed in the same manner as in Reference Example 1 under the atmosphere. The results are summarized in the following table. However, in Reference Example 13, the powder obtained by vacuum drying was immediately evaluated under the atmosphere.

[0415] In the following table, the columns "fine matter containing lithium oxide", "lithium salt" and "water" indicate relative molar ratios. For example, in Reference Example 7, the molar ratio of lithium salt to fine matter containing lithium oxide is 1, and the molar ratio of water to fine matter containing lithium oxide is 11. The above molar ratios were calculated by the following method.

[0416] Regarding the analysis of each element, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the Li salt, and regarding O, the analytical masses of elements other than O were added and calculated as a difference from the total amount of the solid electrolyte. In addition, in Reference Examples 7 and 8, regarding the carbon content, it was estimated based on the analytical mass of sulfur in consideration of each atomic weight in the lithium salt. The molar ratio of the fine matter containing lithium oxide in the solid electrolyte to the lithium salt was calculated based on the molar ratio of the element (e.g., B) present only in the fine matter containing lithium oxide to the element present only in the lithium salt. In addition, the molar ratio of the fine matter containing lithium oxide to water was calculated by subtracting the molar ratio of O contained in the fine matter containing lithium oxide and the lithium salt from the molar ratio of O in the solid electrolyte, and the molar amount of O derived from water was calculated using the obtained molar amount of O derived from water and the molar amount of the fine matter containing lithium oxide.

[0417] [Table 4]

[0418] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 1 0 0 Reference Example 7 1 1 11 Reference Example 8 1 1.2 11 Reference Example 9 1 0.01 4 Reference Example 10 1 0.03 4 Reference Example 11 1 0.5 11 Reference Example 12 1 0.7 11 Reference Example 13 1 1.0 6

[0419] Then, the content (mass %) of each component in the solid electrolyte (I) was calculated based on the molar amount and molecular weight described in Table 4. The results are shown in Table A below.

[0420] [Table A]

[0421] Fine matter containing lithium oxide Lithium salts water Comparative Reference Example 2 100 0 0 Reference Example 7 26 44 30 Reference Example 8 24 48 28 Reference Example 9 70 1 29 Reference Example 10 69 2 29 Reference Example 11 37 20 43 Reference Example 12 34 26 40 Reference Example 13 36 40 24

[0422] [Table 5]

[0423]

[0424] As shown in the above table, the solid electrolyte of each reference example has desired characteristics or properties and exhibits excellent ion conductivity.

[0425] [Manufacturing Example 1] Manufacture of an all-solid-state lithium-ion secondary battery

[0426] <Preparation of fine material containing lithium oxide>

[0427] 45 g of powdered Li2B4O7 crystals (LBO powder) (manufactured by RARE METALLIC Co., Ltd.), 770 g of zirconia beads and 3 mL of water were placed in a 500 mL zirconia jar and sealed with a Teflon gasket and a lid made of zirconia. The LBO powder was pulverized at 300 rpm for 45 hours using a star ball mill to obtain a fine substance containing lithium oxide.

[0428] <Preparation of solid electrolyte slurry>

[0429] 10 g of the lithium oxide-containing fine material, 15 g of water, and 11 g of LiFSI were mixed in a beaker and subjected to ultrasonic treatment for 30 minutes using an ultrasonic cleaner to obtain a dispersion. The dispersion was further stirred for 30 minutes using a magnetic stirrer to obtain a solid electrolyte slurry 1.

[0430] The solid electrolyte slurry 1 was vacuum dried at 40°C and 20Pa for 15 hours to obtain a powder. The obtained powder was stored in a desiccator (5%) for several days and then analyzed in the atmosphere. As a result, it was confirmed that the powder had the above-mentioned X-ray diffraction characteristics and was in an amorphous state. In addition, the ion conductivity was measured by the above-mentioned method and the result was 4.5×10 -3 S / cm. The molar ratio of the content of LiFSI to the content of the lithium-containing oxide is 1, and the molar ratio of the content of water to the content of the lithium-containing oxide is 9. The element composition (molar ratio) is approximately as follows: Li:B:O:F:S:N=3:4:20:2:2:1.

[0431] <Preparation of positive electrode slurry>

[0432] 5.0 g of positive electrode active material LiCoO2 and 4.8 g of a 6 mass % aqueous dispersion of carbon nanotubes (CNT) (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid were added to 5.2 g of the above solid electrolyte slurry 1, and stirred for 30 minutes with a magnetic stirrer to obtain positive electrode slurry 1.

[0433] <Preparation of negative electrode slurry>

[0434] To 7.6 g of the above solid electrolyte slurry 1 were added 5.0 g of negative electrode active material TiNb2O7 and 9.8 g of a 6 mass % aqueous dispersion of CNT (manufactured by KJ Specialty Paper Co., LTD.) as a conductive aid, and stirred for 30 minutes with a magnetic stirrer to obtain negative electrode slurry 1.

[0435] <Preparation of positive electrode stack [solid electrolyte layer / positive electrode active material layer / Al current collector]>

[0436] Using a desktop coater, the above-mentioned positive electrode slurry 1 is coated on an A4-sized Al foil with a thickness of 50 μm at a coating gap of 100 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the above-mentioned solid electrolyte slurry 1 is multi-layered and coated on the positive electrode slurry coating film using a desktop coater with a coating gap of 200 μm and a coating speed of 90 mm / s. The multi-layer coating film is kept in a dryer with a relative humidity of less than 5% for 12 hours for drying, and is punched into a diameter of 10 mm with a manual puncher to obtain a positive electrode side laminate (solid electrolyte layer / positive electrode active material layer / Al collector). In addition, the thickness of the solid electrolyte layer is about 60 μm.

[0437] <Preparation of negative electrode side laminate [solid electrolyte layer / negative electrode active material layer / Al current collector]>

[0438] Using a benchtop coater, the above-mentioned negative electrode slurry 1 is coated on an A4-sized Al foil of 50 μm thick with a coating gap of 200 μm and a coating speed of 30 mm / s. After standing at room temperature for 1 hour, the above-mentioned solid electrolyte slurry 1 is multi-layered and coated on the negative electrode slurry coating film using a benchtop coater with a coating gap of 300 μm and a coating speed of 90 mm / s. The multi-layer coating film is kept in a dryer with a relative humidity of less than 5% for 12 hours for drying, and punched into a diameter of 10 mm with a manual puncher to obtain a negative electrode side laminate (solid electrolyte layer / negative electrode active material layer / Al collector). In addition, the thickness of the solid electrolyte layer is about 60 μm.

[0439] <Manufacturing of all-solid-state lithium-ion secondary batteries>

[0440] (Example 1)

[0441] The above-mentioned negative electrode side laminate was placed on a 10 mm diameter SUS (stainless steel) table of an all-solid-state battery evaluation cell (KP-SolidCell, manufactured by Hohsen Corp.) with the solid electrolyte layer side facing upward. On the solid electrolyte layer, the above-mentioned positive electrode side laminate was placed with the solid electrolyte layer side facing downward. In this way, a laminate of the structure of the positive electrode side laminate / negative electrode side laminate was obtained (the laminate is referred to as a battery cell).

[0442] Next, a Teflon tube with an inner diameter of 10.2 mm was inserted from the positive electrode collector side of the battery cell, a 10 mm diameter, 2 mm thick grinding Ti plate was placed in the hole at the top of the Teflon tube, and the grinding Ti plate was overlapped on the positive electrode laminate. In addition, a Ti rod with a diameter of 10 mm and a height of 2 cm was placed above the grinding Ti plate.

[0443] Next, the upper case of KP-SolidCell was inserted and sealed with double O-rings, four-point bolts and butterfly nuts. The cell was restrained from top to bottom with a torque of 5Nm (equivalent to 30MPa) by the restraining pressure applying mechanism laid on the upper part of KP-SolidCell.

[0444] Next, the KP-SolidCell was opened and the cell was taken out, and the excess liquid components that had seeped out due to the restraining pressure were wiped off. Next, the cell was placed in the KP-SolidCell in the same manner as above, and the cell was restrained from top and bottom.

[0445] Next, each KP-SolidCell was subjected to freeze vacuum drying (10Pa, 40°C) for 2 hours with the upper cover open, thereby fully removing the moisture inside the battery cell. After taking the KP-SolidCell out of the vacuum dryer, the upper cover was closed and sealed with a double O-ring. After being left for 40 hours, it was used as the battery of Example 1.

[0446] (Examples 2 to 4, Comparative Example 1)

[0447] In the manufacture of the battery of Example 1, after placing the Ti rod on top of the polished Ti plate, the amount (number of particles) of silicon dioxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, medium-sized particles (blue)) arranged in the cavity of the KP-SolidCell and the vacuum drying treatment time in the freeze-vacuum drying treatment were set as shown in the table below, and a battery was obtained in the same manner as in Example 1.

[0448] The obtained battery (positive electrode active material mass 2 mg / cm 2 , constraint pressure 30MPa) at 25℃.

[0449] [Test Example] Cycle Characteristics Test

[0450] The battery obtained above was subjected to a restraining pressure (30 MPa) at 27° C. and repeatedly charged and discharged under the following conditions using 580-NOHFR manufactured by TOYO Corporation.

[0451] Charging at a constant current value I β The operation was continued until the battery voltage reached 2.8 V, and after reaching 2.8 V, the operation was continued at a constant voltage (2.8 V) until the current value reached a 2.4C rate.

[0452] After charging, open the circuit and leave it for 10 minutes, thenβ Discharge is performed until the battery voltage reaches 1.5V.

[0453] The charge and discharge up to this point are regarded as one cycle.

[0454] After the discharge, the circuit was opened and left to stand for 10 minutes before the next charge. The charge and discharge were repeated under the same conditions.

[0455] In the above-mentioned charging and discharging, as the initialization of the battery, the current value I β The charge and discharge cycle test was performed by setting the charge to 0.2C and setting the charge and discharge to 3C in the subsequent charge and discharge.

[0456] The results are shown in the following table. In the following table, "water content in KF measurement" in Example 1 and Comparative Example 1 is the water content (mass %) of the laminate composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer, and is determined as follows.

[0457] The obtained battery was disassembled under Ar atmosphere, the cell was taken out, and about 5 to 10 mg of the laminate consisting of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer was sealed in a dedicated vial as a sample. In addition, as a blank, only Ar atmosphere was sealed in a dedicated vial.

[0458] A vial was placed in a water evaporation device for Karl Fischer measurement, heated to 100°C or 300°C to evaporate the water, and then the water content of each sample was measured by Karl Fischer titration using a coulometric water measurement device. The water content of the blank was subtracted from the water content, and the obtained value was divided by the sample amount to obtain the water content (mass %) of the laminate composed of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer.

[0459] [Table 6]

[0460]

[0461] As shown in the above table, it can be seen that the charge and discharge cycle characteristics are effectively improved by vacuum drying the stacked body composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer constituting the battery to suppress the water content.

[0462] The present invention has been described together with its embodiments, but unless otherwise specified, it is understood that the present invention should not be limited to any details in the description and should be broadly interpreted within the scope of the spirit of the invention shown in the attached technical solutions.

[0463] This application claims priority based on Japanese Patent Application No. 2022-089965 filed in Japan on June 1, 2022, the contents of which are incorporated herein by reference as a part of what is described in this specification.

[0464] Explanation of symbols

[0465] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state lithium-ion secondary battery.

Claims

1. An all-solid-state lithium-ion secondary battery, which is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, wherein: The solid electrolyte layer includes an amorphous solid electrolyte, the amorphous solid electrolyte includes a lithium-containing oxide including Li, B and O and a lithium salt, and in the amorphous solid electrolyte, the content of the lithium salt relative to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio, The laminate composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer has a water content of 7.0 mass % or less based on Karl Fischer titration at 100° C., and the difference in water content based on Karl Fischer titration at 100° C. and 300° C. is 0.1 to 5.0 mass %.

2. An all-solid-state lithium-ion secondary battery, which is sequentially configured with a positive electrode layer, a solid electrolyte layer and a negative electrode layer, wherein: The solid electrolyte layer includes an amorphous solid electrolyte, the amorphous solid electrolyte includes a lithium-containing oxide including Li, B and O and a lithium salt, and in the amorphous solid electrolyte, the content of the lithium salt relative to the content of the lithium-containing oxide is 0.001 to 1.5 in terms of molar ratio, The stacked body composed of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer is a stacked body subjected to a vacuum drying treatment.

3. The all-solid-state lithium-ion secondary battery according to claim 1 or 2, wherein: The lithium-containing oxide comprises Li 2+x B 4+y O 7+z , Among them, -0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.

3.

4. The all-solid-state lithium-ion secondary battery according to any one of claims 1 to 3, wherein The lithium salt is represented by the following formula (1): Formula (1) LiN(R f1 SO2)(R f2 SO2) In the formula, R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.

5. The all-solid-state lithium-ion secondary battery according to any one of claims 1 to 4, wherein The lithium-containing oxide is an oxide that has been subjected to mechanical grinding.

6. The all-solid-state lithium-ion secondary battery according to any one of claims 1 to 5, wherein: The all-solid-state lithium-ion secondary battery is an all-solid-state lithium-ion secondary battery formed by sealing a stacked body in which the positive electrode layer, the solid electrolyte layer and the negative electrode layer are sequentially arranged.

7. A method for manufacturing an all-solid-state lithium-ion secondary battery according to any one of claims 1 to 6, comprising the following steps: In the production of the all-solid-state lithium-ion secondary battery, after forming a stacked body including the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer, the stacked body is subjected to a vacuum drying treatment.